2019
DOI: 10.1055/a-1020-3775
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii-associated cholecystitis in a cat receiving immunosuppressive treatment

Abstract: A 9-year-old female neutered domestic shorthair cat diagnosed with immune-mediated thrombocytopenia that was treated with prednisolone and cyclosporine, was presented for anorexia, vomiting, increased liver enzymes, and hyperbilirubinemia. Abdominal ultrasound revealed a markedly thickened gallbladder and common bile duct wall. Bile cytology detected severe neutrophilic inflammation and protozoal zoites. Suspected Toxoplasma gondii infection was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Unmasking latent toxoplasmosis may be a concern with long-term use of high-dose cyclosporine. 206 Toxoplasmosis may be of a greater concern in geographic locations where cats frequently hunt in the wild or consume raw meat and has been reported in renal transplant cats and a cat treated for atopy. [207][208][209] Other immunosuppressive medications, such as chlorambucil, also may be beneficial, but have not been studied in cats with chronic pancreatitis.…”
Section: Anti-inflammatory and Immunosuppressive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Unmasking latent toxoplasmosis may be a concern with long-term use of high-dose cyclosporine. 206 Toxoplasmosis may be of a greater concern in geographic locations where cats frequently hunt in the wild or consume raw meat and has been reported in renal transplant cats and a cat treated for atopy. [207][208][209] Other immunosuppressive medications, such as chlorambucil, also may be beneficial, but have not been studied in cats with chronic pancreatitis.…”
Section: Anti-inflammatory and Immunosuppressive Therapymentioning
confidence: 99%
“…In cats that show a clinical response, continuation of treatment is indicated. Unmasking latent toxoplasmosis may be a concern with long‐term use of high‐dose cyclosporine 206 . Toxoplasmosis may be of a greater concern in geographic locations where cats frequently hunt in the wild or consume raw meat and has been reported in renal transplant cats and a cat treated for atopy 207‐209 …”
Section: Management Of Chronic Pancreatitismentioning
confidence: 99%
“…Cytological examination of bile offers the clinician several advantages such as (1) guiding initial antimicrobial therapy, (2) detection of difficult to culture bacteria (e.g. Helicobacter species), (3) identification of mixed populations of bacteria that can be missed due to being overgrown by E. coli in culture, (4) neutrophilic inflammation in the absence of bacteria is still clinically relevant and (5) non-bacterial pathogens (Platynosomum species, Toxoplasma gondii, Candida albicans) or ( 6) neoplastic cells are occasionally identified (Boomkens et al 2004, Koster et al 2016, Pashmakova et al 2017, Lo Piccolo et al 2019, Palermo et al 2019…”
Section: Neutrophilic Cholangitis/ Cholangiohepatitismentioning
confidence: 99%
“…In five of ten cats that had been treated with cyclosporine at a daily dose of 20 mg/kg q24 h for four weeks, an impairment of the cell-mediated immune response was demonstrated [ 131 ]. It has been shown that cats with high cyclosporine blood concentrations at the time of primary Toxoplasma gondii infection can be at risk of developing systemic toxoplasmosis [ 132 , 133 ], that cats treated with cyclosporine can develop unusual presentations of toxoplasmosis such as Toxoplasma gondii -associated cholecystitis [ 134 ], that latent Toxoplasma gondii infection can be reactivated during treatment [ 135 ], and that in some cats being treated with cyclosporine, toxoplasmosis can be fatal [ 136 ]. Cats receiving cyclosporine are also predisposed to other infections, such as systemic Salmonella spp.…”
Section: Cats Receiving Immunosuppressive Therapymentioning
confidence: 99%